penanggulangan Penanggulangan Sampah Kota Palangka Raya Dengan Menggunakan Model Jaring Perangkap Sampah (Floating Litter Trap) Pada Saluran Drainase: Jaring perangkap sampah efektif dalam penanggulangan dan meminimalisir sampah pada saluran drainase. Jumlah timbulan sampah yang di dapat selama 15 hari yaitu 55,77 kg dengan persentase sampah organik sebesar organik 67,3% dan anorganik 32,7%. Komposisi sampah yang di dapat untuk sampah organik yaitu sayur, buah-buahan, kayu dan ranting pohon adap - Cici Indah Sari; Sari Marlina; Gusti Iqbal Tawakal (Jurnal Teknik SILITEK, 2021)
The increasing population every year also affects the occurrence of waste. The Ministry of Environment and Forestry (KLHK) acknowledges that by 2020 the total national waste production reaches 67.8 million tons per year. Palangka Raya city has several locations where the drainages are filled with waste, especially in densely populated residential areas on Jalan Yos Sudarso km 5.6 so this study is raised from the problems that exist in the city of Palangka Raya that still does not have the handling of waste contained in waterways or drainage, that is, by creating a model of Floating Litter Trap. This research method is using a quantitative descriptive method of calculating the occurrence of waste and the composition of waste and then makes conclusions from the discussion. Floating Litter Trap is effective in tackling and minimizing waste in drainage. The amount of waste that has been collected for 15 days is 55.77 kilograms with a percentage of organic waste 67.3% and inorganic 32.7%. The composition of waste that has been collected, for organic waste namely vegetables, fruits, woods, and tree branches, as for inorganic waste, namely aluminums, plastic bottles, plastic bags, and styrofoams